Strategi Komunikasi Caleg Petahana DPRD Kota Padang - Laila Marni; Emeraldy Chatra; Rahmi Surya Dewi (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2024)
This research aims to understand the communication strategies of incumbent candidates of the Regional House of Representatives in Padang City who were successfully re-elected in the 2024 elections. A qualitative method was used, with three candidate informants and five constituents. The data was analyzed using James E. Grunig's dialogue theory. The main findings reveal three strategies: adjustment of communication language, strengthening emotional relationships, and maintenance of good relations and empathy. This research has important implications for political communication practitioners and researchers. It highlights the significance of two-way communication and public engagement in building relationships between politicians and constituents. It also emphasizes the importance of building emotional relationships and empathy, as they contribute to increased constituent trust and support. Additionally, the research suggests adjusting communication strategies according to constituent characteristics.